Green Corporate Social Responsibility and Sustainable Development Goals Disclosure: The Role of Female Board of Directors - Rizki, Tabah; Widjaja, Andrianto (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2023)
This study aims to analyze the impact of green corporate social responsibility (CSR) on SDGs Disclosure, using female boards of directors as a moderating variable. The study population is manufacturing companies listed on the Indonesian Stock Exchange from 2018 to 2021. This type of research is quantitative. The sampling technique in this study was a targeted sampling method that yielded 68 company observations. The data used is secondary data in the form of corporate reports and sustainability reports. The analytical method in this study is multiple linear regression. The results of this study show that while green CSR positively impacts SDG disclosure, female boards of directors can strengthen the influence of green CSR on SDG disclosure. Overall, the findings of this study provide incentives for companies to strengthen green CSR as part of their competitive advantage strategy to achieve the 2030 SDGs targets.